2013
DOI: 10.1142/s1793525313500192
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Isometries, Boundaries and JSJ-Decompositions of Relatively Hyperbolic Groups

Abstract: We demonstrate the quasi-isometry invariance of two important geometric structures for relatively hyperbolic groups: the coned space and the cusped space. As applications, we produce a JSJ-decomposition for relatively hyperbolic groups which is invariant under quasi-isometries and outer automorphisms, as well as a related splitting of the quasiisometry groups of relatively hyperbolic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…As mentioned above, Bowditch showed that for a one‐ended hyperbolic group G which is not cocompact Fuchsian the existence of a local cut point is equivalent to a splitting of G over a two‐ended subgroup. Generalizations of Bowditch's results have been studied by Papasoglu–Swenson , and Groff for CAT(0) and relatively hyperbolic groups, respectively.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…As mentioned above, Bowditch showed that for a one‐ended hyperbolic group G which is not cocompact Fuchsian the existence of a local cut point is equivalent to a splitting of G over a two‐ended subgroup. Generalizations of Bowditch's results have been studied by Papasoglu–Swenson , and Groff for CAT(0) and relatively hyperbolic groups, respectively.…”
Section: Introductionmentioning
confidence: 89%
“…Using cut pairs instead of local cut points Groff obtains a partial extension of Bowditch's JSJ tree construction for relatively hyperbolic groups, and Guralnik observed that in the special case that the relative boundary (Γ,P) has no global cut points, then many of Bowditch's results about the valence of local cut points in the boundary of a hyperbolic group translate directly to the relatively hyperbolic setting. Their results were subsequently used by Groves and Manning to show that if (Γ,P) has no global cut points and all the peripheral subgroups are one‐ended, then the existence of a local cut point in (Γ,P) is equivalent to the existence of a splitting of normalΓ relative to double-struckP over a non‐parabolic 2‐ended subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…(See [6] for a complete proof.) A recent paper of Groff [15] extends this theorem to show that the Bowditch boundary of a relatively hyperbolic group is also well-defined up to quasi-isometry.…”
Section: Introductionmentioning
confidence: 90%
“…Moreover the maximal parabolic groups are precisely the peripheral subgroups; by Theorem 2.9 and since conical limit points cannot be parabolic these are all bounded, and in particular the stabiliser of each bounded parabolic point is finitely-generated (Proposition 6. 13) We summarize all of this in a statement that will be used again in the next section: Proposition 6.14. -Given a representation ρ : Γ → GL(d, R) which is 1-dominated relative to P, ρ(Γ) acts on Λ rel as a geometrically-finite convergence group, with P Γ as the set of maximal parabolic subgroups.…”
Section: Summary Of Argumentmentioning
confidence: 99%